Protocolo clínico para o manejo do HIV, Sífilis, Hepatites B e C na população privada de liberdade - Nunes, Sabrina Freitas (2025)
The objective of this study is to adapt clinical protocols for the management of Sexually Transmitted Infections/Human Immunodeficiency Virus in the Prison Population. This is a methodological study, developed from January 2024 to February 2025, to be implemented in prison units in the state of Ceará. The steps proposed by ADAPTE for construction through adaptation were followed, in three stages: Configuration, Adaptation, and Finalization. In the configuration phase, the feasibility of the adaptation was defined through literature searches and visits to prison units, and multidisciplinary work groups with clinical and academic expertise in health in the context of deprivation of liberty, and/or in Sexually Transmitted Infections were formed. For the adaptation, an integrative review was carried out that recovered eight protocols/guidelines, predominantly in English and similarly distributed among the MS, WHO, BOP, PAHO, and CDC. The AGREE-II tool showed variable methodological quality among the documents, with emphasis on the WHO, CDC and PAHO. The evaluation of the recommendations for prevention, screening, diagnosis and treatment were summarized in terms of differences and similarities, and were selected and adapted to the Brazilian reality by the group of 10 panelists. Of the recommendations included, the biggest changes were in prevention, in which Opioid Substitution Therapy, Needle and Syringe Exchange, Accelerated Partner Therapy and Medical Male Circumcision have legal, structural and economic barriers to implementation, and were therefore not considered. For screening, the recommendations of the Ministry of Health and the rapid testing indicated for this population were standardized; for diagnosis, the therapeutic options indicated by the Ministry of Health were considered, considering the feasibility of resources and techniques applied in the country, as well as for treatment, which considered those made available by the Brazilian health system. The final phase, the finalization phase, was carried out with external members, five professionals from nursing, pharmacy, medicine and psychology working in the system, who collaborated in the evaluation. After evaluation via form, a new chapter was created including more specificities of the state of Ceará, and condoms were restricted to vulnerable groups and risk practices; as well as health education for peers, which was removed due to the risk of violence between people with some comorbidity from different factions. Thus, the protocol has 16 chapters, distributed among prevention, screening, treatment and diagnosis of HIV, Syphilis and Hepatitis, and related to legal issues and organization of the material. The adaptation of the guidelines proposes an evidence-based model to qualify these STIs in prison units, contributing to the quality and effectiveness of care.